An An Overview of Stress Levels Among Post Stroke Patients in the Wonoayu Public Health Center Area Sidoarjo Regency - Nadiya Arifa Rahma; Luluk Widarti; Suprianto; Siti Maemonah (Global Ten Public Health and Nursing Journal, 2025)
The long term effects of stroke extend beyond physical limitations, frequently involving psychological challenges such as stress. Persistent stress may interfere with recovery and diminish life quality. This research focuses on identifying stress levels in post stroke individuals served by Wonoayu Public Health Center in Sidoarjo. Research method applied was quantitative with descriptive approach and cross-sectional design. Sampling technique employed purposive sampling, involving 38 respondents. Stress levels were assessed using DASS-42 stress subscale. Results showed most respondents experienced mild stress (27 individuals; 71%), followed by moderate stress (4 individuals; 11%) and severe stress (7 individuals; 18%). The characteristics of respondents who tended to experience stress were young adult females, with a history of one stroke attack, and had suffered from stroke for more than one year. The Conclusion of this study highlights the importance of paying attention to psychological factors in the recovery process of post-stroke patients, especially in vulnerable groups. Nurses are expected to provide appropriate psychological interventions to support optimal recovery.